Migration and Livelihood: A Case Study Sahid Lakhan Gaupalika, Gorkha - K.C., Arjun (Journal of Rapti Babai Campus, 2025)
Migration is defined as movement of people from own country, place or locality to another in search of better opportunities. Migration has been an important social process of human history, where people have been moving from one place to another in search of livelihood. This study looks at the relationship between migration and livelihood in Sahid Lakhan Gaupalika of Gorkha District in Nepal.Concerning the research methodology, a cross-sectional survey design was employed, which only sought information at one point of data collection to determine migration aspects in the selected study area, as well as the adopted livelihood activities. Purposive sampling was used in which 65 respondents were selected using closed questionnaires. The nature of data was primary and quantitative which helped in presenting deeper picture of the existing issues and factors the study aimed at collecting rich data on migration and livelihoods in Sahid Lakhan Gaupalika.In this study it is revealed that economic reasons particularly job seeking are found to be the main cause of migration and then come education mission and finally joining of family members. Migration has significantly impacted the people’s way of living through increased employment opportunities in the formal sector and decreased employment opportunities in agriculture. This paper contributes to knowledge in the area of migration and its impact on the livelihoods with a view of informing policy and practice for the enhancement of the positive effects of migration and the minimization of the negative effects.